2022
DOI: 10.1101/2022.01.26.477664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing identifies phenotypically, functionally, and anatomically distinct stromal niche populations in human bone marrow

Abstract: Hematopoiesis is regulated by the bone marrow (BM) stroma. However, cellular identities and functions of the different BM stromal elements in humans remain poorly defined. Based on single-cell RNA sequencing, we systematically characterized the BM stromal compartment which led to the identification of six transcriptionally and functionally distinct stromal cell populations. Stromal cell differentiation hierarchy was recapitulated based on RNA velocity analysis, in vitro proliferation capacities and differentia… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Similarly, Buechler et al (2021) illustrated the compartmentalisation of the murine fibroblast lineage into universal, specialised and activated subtypes, whereby a universal/common ancestor fibroblast population gives rise to tissue-specific specialised subtypes (steady state) that may acquire an activated phenotype during disease/infection. Based on these studies, scRNA-seq of human bone marrow stroma (CD45 low/À CD235a À CD271 + ) identified six stromal cell types across nine clusters, which included pre-fibroblasts and multipotent stromal stem cells (Li et al, 2022).…”
Section: Characterisation Of Distinct Fibroblast and Mesenchymal Stem...mentioning
confidence: 99%
“…Similarly, Buechler et al (2021) illustrated the compartmentalisation of the murine fibroblast lineage into universal, specialised and activated subtypes, whereby a universal/common ancestor fibroblast population gives rise to tissue-specific specialised subtypes (steady state) that may acquire an activated phenotype during disease/infection. Based on these studies, scRNA-seq of human bone marrow stroma (CD45 low/À CD235a À CD271 + ) identified six stromal cell types across nine clusters, which included pre-fibroblasts and multipotent stromal stem cells (Li et al, 2022).…”
Section: Characterisation Of Distinct Fibroblast and Mesenchymal Stem...mentioning
confidence: 99%